2020
DOI: 10.4038/jccpsl.v25i4.8208
|View full text |Cite
|
Sign up to set email alerts
|

Adherence to infection control practices in relation to neonatal care in major hospitals in a district of Sri Lanka

Abstract: Introduction: Adherence to infection control practices are crucial for neonatal care.Objectives: To describe the adherence to clean birth and postnatal care practices by healthcare workers in selected procedures in major hospitals in a district of Sri Lanka Methods:This was a qualitative observational study. The study sample comprised healthcare workers (doctors, nurses and midwives) attached to the labour room (LR), postnatal ward (PNW), neonatal intensive care unit (NICU) and operating theatre (OT). A total … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 5 publications
1
1
0
Order By: Relevance
“…It was observed in this study that in view of 396 opportunities to use gloves, only one (0.25%) of them occurred in agreement with all the necessary steps, including the correct hand hygiene. This low adherence to HH by nursing professionals is corroborated by the literature in several countries (8,(12)(13) .…”
Section: Discussionsupporting
confidence: 59%
See 1 more Smart Citation
“…It was observed in this study that in view of 396 opportunities to use gloves, only one (0.25%) of them occurred in agreement with all the necessary steps, including the correct hand hygiene. This low adherence to HH by nursing professionals is corroborated by the literature in several countries (8,(12)(13) .…”
Section: Discussionsupporting
confidence: 59%
“…In Sri Lanka, a research (13) that aimed to describe adherence to infection control practices in relation to neonatal care by nursing team and physicians, found that HH before the use of gloves was performed by 33.3% of professionals in the operating room (before handling neonates) and 57.1% in the delivery room, unlike those working in the Neonatal Intensive Care Unit, in which the percentage was quite satisfactory, 96%. Despite the knowledge about the stages and the importance of HH seem to be something well established for the nursing team, other factors can influence, such as an intensive care environment, which can give the professionals who work in it the false impression that HH is more necessary as it is an imminent risk sector.…”
Section: Discussionmentioning
confidence: 99%